Evaluating chronic disease management in real-world settings in six European countries: Lessons from the collaborative DISMEVAL project. (June 2014) - Elissen, Arianne; Nolte, Ellen; Hinrichs, Saba; Conklin, Annalijn; Adams, John; Cadier, Benjamin; Chevreul, Karine; Durand-Zaleski, Isabelle; Erler, Antje; Flamm, Maria; Frølich, Anne; Fullerton, Birgit; et al.
Objective: To describe the interventions, research methods and main findings of the international DISMEVAL project, in which the "real-world" impact of exemplary European disease management approaches was investigated in six countries using advanced analytic techniques. Design: Across countries, the project captured a wide range of disease management strategies and settings; approaches to evaluation varied per country, but included, among others, difference-in-differences analysis and regression discontinuity analysis. Setting: Austria, Denmark, France, Germany, The Netherlands, and Spain. Participants: Health care providers and/or statutory insurance funds providing routine data from their disease management interventions, mostly retrospectively. Intervention(s): This study did not carry out an intervention but evaluated the impact of existing disease management interventions implemented in European care settings. Main outcome measure(s): Outcome measures were largely dependent on available routine data, but could concern health care structures, processes, and outcomes. Results: Data covering 10 to 36 months were gathered concerning more than 154, 000 patients with three conditions. The analyses demonstrated considerable positive effects of disease management on process quality (Austria, Germany), but no more than moderate improvements in intermediate health outcomes (Austria, France, Netherlands, Spain) or disease progression (Denmark) in intervention patients, where possible compared with a matched control group. Conclusions: Assessing the "real-world" impact of chronic disease management remains a challenge. In settings where randomization is not possible and/or desirable, routine health care performance data can provide a valuable resource for practice-based evaluations using advanced analytic techniques.